PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TAPPS TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS DITINJAU DARI DISPOSISI MATEMATIS - Yuli Rahmawati; Hariaty Hamid; Maharani Izzatin (Mathematics Education And Application Journal (META), 2019)
This research aims to determine the influence of cooperative learning models (TAPPS and conventional type) on mathematical critical thinking ability, the influence of high and low mathematical disposition on mathematical critical thinking abilities, and the influence of interactions between learning models (TAPPS and conventional type) with students’ mathematical disposition on mathematical critical thinking skills in eighth grader of SMP Negeri 7 Tarakan. This research was carried out in the odd semester of 2018/2019 school year in SMP Negeri 7 Tarakan. The type of research used in this study is a quasi-experimental with a 2×2 factorial design. The population in this study were all eighth grade students of SMP Negeri 7 Tarakan. Sampling is done by simple random sampling. The sample in this study is class VIII-1 as a control class and VIII-3 as an experimental class. Data collection is done by using mathematical critical thinking ability test and mathematical disposition questionnaire. Data analysis techniques using descriptive and inferential analysis. Descriptive analysis includes mean and standard deviation. Inferential analysis uses two-way variance analysis. Based on the results of the analysis with a significant level of 5%, it can be concluded that the learning model (TAPPS and conventional) influenced the ability of  mathematical critical thinking with p-value 0.046, high and low mathematical disposition affect the ability of mathematical critical thinking with a p-value of 0.000, and there is no influence of interaction between learning models with mathematical disposition of mathematical critical thinking skills in class VIII SMP 7 Tarakan with p-value 0.503.